2015
DOI: 10.24015/japm.2015.0017
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Effectiveness of Reduced Red Blood Cells Consumption in Spine Surgery under the Guidance of West China Perioperative Transfusion Score (WCPTS): A Prospective, Randomized, Controlled Trial

Abstract: Background: Transfusion trigger and target for surgical patients with hemoglobin (Hb) level between 7-10 per deciliter is not available worldwide, and the decision of whether red blood cells (RBCs) should be administered in these patients is made according to the experience of clinicians without evidences. Based on the physiology of the balance between oxygen supply and consumption, we suggested West China Perioperative Transfusion Score (WCPTS) to be safely applied to the patients undergoing spine surgery wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 5 publications
0
9
1
Order By: Relevance
“…In a previous trial in patients undergoing elective spine surgery with expected blood loss more than 800 ml or exceeding 20% total blood volume, 6,45 In contrast to reduced transfusion volume with POTTS in a previous trial by Zhu et al, 46 transfusion volume did not differ between the two groups in the current study. Such a discrepancy may be attributed to several reasons, including higher percentage of transfusion due to higher percentage of patients with cancer in the previous trial, and the use of intraoperative blood salvage in the current study.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…In a previous trial in patients undergoing elective spine surgery with expected blood loss more than 800 ml or exceeding 20% total blood volume, 6,45 In contrast to reduced transfusion volume with POTTS in a previous trial by Zhu et al, 46 transfusion volume did not differ between the two groups in the current study. Such a discrepancy may be attributed to several reasons, including higher percentage of transfusion due to higher percentage of patients with cancer in the previous trial, and the use of intraoperative blood salvage in the current study.…”
Section: Discussioncontrasting
confidence: 73%
“…In a previous trial in patients undergoing elective spine surgery with expected blood loss more than 800 ml or exceeding 20% total blood volume, 6,45 the rate of RBCs transfusion was 36.5% in the POTTS group versus 89.4% in the control group with liberal transfusion strategy. The current study compared POTTS versus restrictive blood transfusion, a strategy recommended by major guidelines and widely used in clinical practice.…”
Section: Discussionmentioning
confidence: 94%
“…We also set the power to be 90% for each outcome. In our pilot study comparing transfusion guided by individualized and liberal transfusion strategy, we found that among 191 of patients, 36.5% in the individualized group and 89.4% in the liberal group (P<0.001) received red cells transfusion in perioperative period, and a median of zero units of red cells were transfused in the individualized group and 3.5 units in the liberal group (P<0.001) (8). Besides, we sampled 400 records of blood transfusion in spine surgeries with blood loss more than 800 ml from 2006 to 2009 in West China Hospital, Sichuan University, and found that 76.7% patients received red cells transfusion and the number of transfused Red cells units was 2.7 U on average.…”
Section: Sample Size and Statistical Analysismentioning
confidence: 89%
“…[14] This semi-quantitative score could be applied by any physician without complex measurements. [10,15] Above all, the pediatric individual transfusion strategy was designed in order to reduce perioperative blood exposure in children. The reason why this strategy was able to reduce the amount of RBC transfusion may be multifactorial.…”
Section: Discussionmentioning
confidence: 99%
“…We conducted a clinical trial of adult patients with spinal surgery and the results suggested this individualized strategy was safe and costeffective. [10] Based on this score, taking account of children's age and developmental stage, we designed a Pediatric Perioperative-Transfusion-Trigger Score (Pediatric-POTTS) (Table 1) to guide transfusion in children. We designed this trial to test the hypothesis that transfusion guided by the individualized strategy could decrease exposure to blood, without increasing perioperative complications in children.…”
mentioning
confidence: 99%